Wirklichkeit oder Konstruktion? Sprachtheoretische und interdisziplinäre Aspekte einer brisanten Alternative - Felder, Ekkehard (De Gruyter, 2018)
Do we have true access to reality or are we merely surrounded by our own constructions of reality? This classic question has been taken up again with great urgency in the sciences and by the media. The volume reflects on the current status of the controversy, presenting essays by renowned proponents from different disciplines.